Supporting the Surviving Parent to Support their Bereaved Children: a psycho-educational group for parents - Finucane, Niamh; Concannon, Noirin (Groupwork, 2020)
This paper describes the rationale for developing a psycho-educational group about supporting bereaved children. The group is for surviving parents following the death of their partner. As social workers in a specialist palliative care setting, we noticed a similarity in the concerns and questions raised by the surviving parents the social work team met with. It is broadly recognised that there are distinct difficulties for children losing a parent and caregiver, as this is often the person that previously was central in the provision of love, security and daily care. It is well documented that the adjustment of the surviving caregiver and the quality of care received by the child after the loss, are substantially related to how children cope (The Harvard Child Bereavement Study, 1996). Studies revealed that when parents are supported, they can demonstrate an enhanced capacity to support their children. The group provided guidance on how to support their bereaved children. The importance of creating a support network for families by connecting them with others who have experienced similar events is well documented in the literature and was also a significant rationale for developing the programme. Keywords: parental death; childhood bereavement; surviving parent; psycho-educational group